Landing-related ankle injuries do not occur in plantarflexion as once thought: a systematic video analysis of ankle injuries in world-class volleyball - Skazalski, C.; Kruczynski, J.; Bahr, M. A.; Bere, T.; Whiteley, R.; Bahr, R. (British Journal of Sports Medicine, 2018)
Background: Ankle injuries are prevalent in elite volleyball and suggested to result from player contact at the net. Traditionally, ankle sprains are thought to happen in a plantarflexed position, but case studies suggest plantarflexion may not be involved.